2022
DOI: 10.3390/antib11040069
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Anti-SARS-CoV-2 Antibodies in Chattogram Metropolitan Area, Bangladesh

Abstract: Seroprevalence studies of COVID-19 are used to assess the degree of undetected transmission in the community and different groups such as health care workers (HCWs) are deemed vulnerable due to their workplace hazards. The present study estimated the seroprevalence and quantified the titer of anti-SARS-CoV-2 antibody (IgG) and its association with different factors. This cross-sectional study observed HCWs, in indoor and outdoor patients (non-COVID-19) and garment workers in the Chattogram metropolitan area (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
3
0
0
Order By: Relevance
“…Note that positivity thresholds differ slightly between experiment with serum ( Fig 4B ) and whole blood (Figs 4C and 5A–5C ) due to differences in optical absorption of the sample, and are determined separately (Methods). Although seroprevalence across regional populations may exhibit complex spatiotemporal dynamics, our results are in approximate concordance with previous studies of seroprevalence in Bangladesh residents [ 32 , 33 ].…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Note that positivity thresholds differ slightly between experiment with serum ( Fig 4B ) and whole blood (Figs 4C and 5A–5C ) due to differences in optical absorption of the sample, and are determined separately (Methods). Although seroprevalence across regional populations may exhibit complex spatiotemporal dynamics, our results are in approximate concordance with previous studies of seroprevalence in Bangladesh residents [ 32 , 33 ].…”
Section: Resultssupporting
confidence: 92%
“…For example, a study in the United States [ 39 ] found that 43.7% of adults with “serology results indicative of past infection…reported never having had COVID-19, possibly representing asymptomatic infection”, suggesting that self-reported infection data in general may not correlate well with serological findings. Similarly, previous studies in Bangladesh measured majority seropositivity fractions concordant with our own data [ 32 , 33 ], both of which suggest much higher rates of exposure than indicated by self-reporting.…”
Section: Resultssupporting
confidence: 92%
“…Note that positivity thresholds differ slightly between experiment with serum (Figure 4b) and whole blood (Figure 4c and Figure 5a-c) due to differences in optical absorption of the sample, and are determined separately (Methods). Although seroprevalence across regional populations may exhibit complex spatiotemporal dynamics, our results are in approximate concordance with previous studies of seroprevalence in Bangladesh residents [32,33].…”
Section: Recording Serological Prevalence Of Sars-cov-2 In Bangladeshsupporting
confidence: 92%